Hacia una nueva lógica del populismo: De la ruptura de las instituciones a la institucionalidad populista - Cadahia, María Luciana (2020)
This article aims to study the relationship between institutional policies and populism analyzing the Universal Assignment for Child (AUH) in Argentina. To achieve this objective we will divide the paper in three sections. Firstly, we will think the populist moment in this particular setting as a method of interpretation. Secondly, we will follow the theoretical debates about institutions and populism explaining the difficulty to think this relationship. Third, from the concrete case of AUH, in order to show the constitutive moments: the emergence of popular demand, its appropriation and processing by the government and the transformation of demand into a right. Finally, we will show how the rupturist conflict of populist institutionalism helps us conceive a transnational alternative to global neoliberalism.